Taxonomic notes on the Alocasia-Colocasia Clade (Araceae) in China I: Alocasia yunqiana, a new species from Tongbiguan Nature Reserve, Yunnan Province - Ma, Zhengxu; Li, Yifan; Dao, Baohui; Yang, Wanliu; Liu, Bing; Yin, Jian-Tao (Phytotaxa, 2020)
A new Alocasia species, Alocasia yunqiana, is described and compared with its morphologically related taxa. The novelty is characterized by an oblong-naviculiform-shaped spathe-limb that is strongly hooded and slightly glaucous to glossy during its entire anthesis, a spadix with a sterile interstice and an appendix that are much shorter and thinner than the staminate zone, as well as the dimorphic synandroidia. Detailed information containing description, colored plates and illustration are provided herein.